Selfies in 'mommyblogging': An emerging visual genre. (December 2017) - Zappavigna, Michele; Zhao, Sumin
Abstract: This article employs multimodal discourse analysis to explore how mothers represent their everyday experiences of motherhood on Instagram through different forms of self-portraiture. It investigates whether the 'selfies' that they share can be characterized as a visual genre and identifies four subgenres: presented, mirrored, inferred and implied selfies. The article illustrates the different ways in which the photographer's perspective can be represented in each subgenre. The aim is to show that the function of the selfie as a multimodal genre is not solely to represent 'the self' but rather to enact intersubjectivity, that is, to generate various possibilities of relations between perspectives on a particular topic, issue, or experience and hence to open up potential for negotiating different points of view.